2005
DOI: 10.1091/mbc.e04-02-0089
|View full text |Cite
|
Sign up to set email alerts
|

Methylator-induced, Mismatch Repair-dependent G2Arrest Is Activated through Chk1 and Chk2

Abstract: 2 /M arrest and how MMR mechanistically participates in this process are unknown. Here, we show that MNNG exposure results in activation of the cell cycle checkpoint kinases ATM, Chk1, and Chk2, each of which has been implicated in the triggering of the G 2 /M checkpoint response. We document that MNNG induces a robust, dose-dependent G 2 arrest in MMR and ATM-proficient cells, whereas this response is abrogated in MMR-deficient cells and attenuated in ATM-deficient cells treated with moderate doses of MNNG. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 66 publications
9
71
2
Order By: Relevance
“…The medium was subsequently concentrated using iCON concentrators (Pierce, Rockford, IL) and protein concentration was assayed by BCA (Pierce). SDS-PAGE and immunoblotting was done using established protocols (36). Biotinylated goat anti-human cystatin E/M antibody was purchased from R&D Systems (Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
“…The medium was subsequently concentrated using iCON concentrators (Pierce, Rockford, IL) and protein concentration was assayed by BCA (Pierce). SDS-PAGE and immunoblotting was done using established protocols (36). Biotinylated goat anti-human cystatin E/M antibody was purchased from R&D Systems (Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
“…A number of interactions between MMR proteins and DNA damage signalling proteins have been reported including interactions between MSH2 and ATR, Chk1 and Chk2 (Wang and Qin, 2003;Yoshioka et al, 2006); MLH1 and ATM (Adamson et al, 2005;Brown et al, 2003); PMS2 and p73 (Shimodaira et al, 2003); the three MutL homologues, MLH1, PMS2, and PMS1 with a large number of proteins involved in cell cycle/signalling/apoptosis functions (Cannavo et al, 2007). The challenge is to determine the functional significance of these interactions and the biological context in which they operate.…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 99%
“…This requires hMutS and hMutL complexes and may involve direct interactions between hMLH1 and ATM, as one signaling complex, and hMSH2 and Chk2 as another (Brown et al, 2003). In response to certain DNA damaging adducts, such as O 6 -methylguanine, hMSH2 has been found to engage in a direct signaling complex with ATR, indicating that MMR can act as damage sensors for ATR-dependent checkpoint signaling (Wang and Qin, 2003;Yamane et al, 2004;Adamson et al, 2005;Yoshioka et al, 2006). Additionally, it has been shown that hMLH1 is necessary for p53-mediated induction of apoptosis in response to alkylating and oxygen radicalinducing agents (Luo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%